2022
DOI: 10.1002/acr.24545
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Allergy Symptoms in IgG4‐Related Disease: A Case–Control Study

Abstract: Objective. The etiology of IgG4-related disease (IgG4-RD) is unknown, and there has been controversy over the significance of allergic conditions in IgG4-RD. We examined the prevalence of lifetime allergy symptoms in IgG4-RD and the association between these and IgG4-RD.Methods. We identified IgG4-RD patients and non-IgG4-RD controls without autoimmune conditions seen at a single center. IgG4-RD patients were classified using the American College of Rheumatology/European Alliance of Associations for Rheumatolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Originally, an association between IgG4-RD and allergic diseases was suggested 1,13,14 . However, some more recent studies have indicated that allergic symptoms are not more frequent in IgG4-RD as compared to several control populations despite the common findings of serum IgE elevation and peripheral blood eosinophilia in the former [15][16][17] . Accordingly, any association of allergic predisposition with IgG4-RD pathogenesis or disease deterioration is yet unproven and remains to be clarified through further investigations.…”
Section: Discussionmentioning
confidence: 89%
“…Originally, an association between IgG4-RD and allergic diseases was suggested 1,13,14 . However, some more recent studies have indicated that allergic symptoms are not more frequent in IgG4-RD as compared to several control populations despite the common findings of serum IgE elevation and peripheral blood eosinophilia in the former [15][16][17] . Accordingly, any association of allergic predisposition with IgG4-RD pathogenesis or disease deterioration is yet unproven and remains to be clarified through further investigations.…”
Section: Discussionmentioning
confidence: 89%
“…To assess sensitivity of algorithms, we identified patients from the MGH Center for IgG4-RD registry who were enrolled in Medicare Fee-for-Service with Part A, B, and D coverage during the study period after the initial date of their IgG4-RD diagnosis. The MGH Center for IgG4-RD maintains a registry of all patients evaluated who have IgG4-RD confirmed to be definite, probable, or atypical according to the American College of Rheumatology (ACR) and European League Against Rheumatism (EULAR) classification criteria for IgG4-RD and previously described methods (7)(8)(9). This study was approved by the MGB Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Two authors (ZSW and JHS) reviewed cases identified by each algorithm and determined whether they were IgG4-RD on the basis of the classification criteria approved by the EULAR and ACR (7). We included patients who fell into one of three categories: 1) definite IgG4-RD, 2) probable IgG4-RD, and 3) atypical IgG4-RD (8,9). Patients in the definite category fulfilled the published classification criteria.…”
Section: Significance and Innovationmentioning
confidence: 99%
“…this phenotype compared with others. 4,[6][7][8]34 Juvenile-onset IgG4-RD patients present more frequently with this phenotype. 35,36 Clinical, serological, radiological, and histological correlation is of paramount importance to diagnose this phenotype due to the myriad of differential diagnoses (Table ).…”
Section: Head and Neck Limited Phenotypementioning
confidence: 99%